MicroRNAs: Non-coding fine tuners of receptor tyrosine kinase signalling in cancer. (February 2016) - Donzelli, Sara; Cioce, Mario; Muti, Paola; Strano, Sabrina; Yarden, Yosef; Blandino, Giovanni
Abstract: Emerging evidence point to a crucial role for non-coding RNAs in modulating homeostatic signaling under physiological and pathological conditions. MicroRNAs, the best-characterized non-coding RNAs to date, can exquisitely integrate spatial and temporal signals in complex networks, thereby confer specificity and sensitivity to tissue response to changes in the microenvironment. MicroRNAs appear as preferential partners for Receptor Tyrosine Kinases (RTKs) in mediating signaling under stress conditions. Stress signaling can be especially relevant to disease. Here we focus on the ability of microRNAs to mediate RTK signaling in cancer, by acting as both tumor suppressors and oncogenes. We will provide a few general examples of microRNAs modulating specific tumorigenic functions downstream of RTK signaling and integrate oncogenic signals from multiple RTKs. A special focus will be devoted to epidermal growth factor receptor (EGFR) signaling, a system offering relatively rich information. We will explore the role of selected microRNAs as bidirectional modulators of EGFR functions in cancer cells. In addition, we will present the emerging evidence for microRNAs being specifically modulated by oncogenic EGFR mutants and we will discuss how this impinges on EGFRmut driven chemoresistance, which fits into the tumor heterogeneity-driven cancer progression. Finally, we discuss how other non-coding RNA species are emerging as important modulators of cancer progression and why the scenario depicted herein is destined to become increasingly complex in the future.